The effect of converting conventional diesel-fueled tractors to a hybrid drive system on fuel consumption and CO2 emission - Balci, Ozgun; Karagoz, Yasin (TAYLOR & FRANCIS INC, 2026)
Nowadays, the majority of tractors are powered by old-fashioned technologies, namely diesel engines equipped with mechanical fuel injection systems. Nonetheless, the increasing cost of fuel and engines, coupled with the enforcement of stringent emission regulations, has prompted researchers to take measures to develop and preserve hybrid drive systems. In this study, a 3-cylinder hybrid diesel tractor engine was numerically converted to a hybrid system using the MATLAB/Simulink environment, which plays a pivotal role in this process. The hybrid control strategy was implemented in conjunction with the ECMS method. The dataset, which included a speed-time graph of a tractor towing a 5-ton trailer, was acquired. On the other hand, fuel consumption and CO2 emission data were obtained from the model stored in the MATLAB/Simulink environment. The results clearly demonstrate that employing the hybrid drive system with the ECMS method led to significant fuel consumption reduction from 25.4 L/100 km to 23.1 L/100 km and CO2 emission reduction from 626.7 g/km to 570.9 g/km.
Keywords: CO2; ECMS; emission; fuel economy; hybrid tractor; Energy & Fuels; Engineering; Environmental Sciences & Ecology